Interpretative Boundaries in Civil Execution: Repositioning the Enforcement Force of Judicial Dicta - Lastri Yasim (Kirana Publisher (KNPub), 2026)
This article critically examines the normative boundaries governing judicial enforcement in civil procedure, focusing on the locus of enforcement authority in the operative part (dicta) of civil judgments. The study investigates the extent to which interpretative reliance on judicial reasoning (legal grounds) is permissible within enforcement processes without expanding the scope of the operative command. Employing a doctrinal legal methodology, this research analyzes statutory texts, principles of legal certainty, and contemporary debates in enforcement law. Findings illustrate that execution authority fundamentally attaches to the operative part of the judgment, while interpretative use of judicial reasoning should be strictly limited to clarifying ambiguous orders without introducing additional coercive measures. This position reinforces legal certainty and due process, especially in cases involving property execution and third party rights. The article contributes to the ongoing discourse on the rule of law and enforcement discretion by outlining a principled framework that respects enforcement constraints within civil procedure.